Navigating the ethical terrain of spiritually focused psychotherapy goals: multiple worldviews, affective triggers, and personal practices - Keenan, Elizabeth King (Smith College Studies in Social Work, 2010)
Constructing mutual, spiritually focused psychotherapy goals is a practice activity fraught with numerous ethical and countertransferential challenges. This article seeks to inform the thinking and enhance the ability of clinical social workers to engage in collaborative and responsive dialogues with their clients regarding the goals of spiritually focused clinical practice by (1) identifying the multiple value frameworks that influence decisions regarding practice goals, (2) articulating some of the ethical complexities and common countertransferential reactions associated with goal setting, and (3) providing self-reflection questions and guides to help therapists navigate the complexities of this material.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-323-659-562-624 tex.article-number: [object Object] tex.unique-id: [object Object]
Keywords: Countertransference; Ethics; Goals; Piritually focused psychotherapy; dept.swk